Northern Shrimp (Pandalus borealis) on Flemish Cap in June 2003 - Río-Iglesias, José Luis del; Casas-Sánchez, José Miguel; González-Troncoso, Diana (2003)
Since 1988, a stratified random summer bottom trawl survey in Flemish Cap (NAFO Regulatory Area of Div. 3M) was conducted by UE. In June 2003, the survey was carried out by the new research vessel R/V Vizconde de Eza. For this reason during the first ten days of the survey a comparative Fishing Trial (calibration) was conducted between the old research vessel R/V Cornide de Saavedra and the new research vessel R/V Vizconde de Eza in order to calibrate the new ship. The corresponding Factor Power Correction (FPC) was calculated by generalized linear regression model by haul, and a length conversion method. The transformed entire series of abundance, biomass, mean catch per tow and length distribution for northern shrimp (Pandalus borealis) are presented for the period 1988-2002, and the no-transformed data for the year 2003. Also the standard error was shown for mean catch per tow. This year a decreasing in shrimp biomass was observed. It was mainly due to declining of female biomass. Also the youngest model group (age 1) appeared well represented, predicting a good recruitment in next years. However, all these results must be taken carefully because the scarce number of hauls carried out during the calibration.